ETIKA PROFESIONAL, INDEPENDENSI DAN TEKANAN WAKTU TERHADAP KUALITAS REVIU LAPORAN KEUANGAN (STUDI KASUS PEMERINTAH DAERAH KABUPATEN PINRANG) - Subur, Sugiarti (Economos : Jurnal Ekonomi dan Bisnis, 2019)
This research was conducted with the aim of: (1) Analyzing the effect of auditor professional ethics on the quality of the review the financial statement of the Pinrang District Government; (2) Analyzing the effect of independence on the quality of the reviewthe financial statement of the Pinrang District Government; (3) Analyzing the effect of time pressure on the quality of the review the financial statement of the Pinrang District Government.This research use a questionnaire in the form of statements given to the Staff of the Inspectorate Office of the Pinrang Distric Government as many37 respondents as sample of all the number of employees in the Inspectorate Office of the Pinrang District Government as many47 people. Data were analyzed using the SPSS program (Statistical Package For Social Science) version 24.0.The results of this research indicate that: (1) Auditor Professional ethics has a positive and significant effect on the quality of the review the financial statement of the Pinrang District Government; (2) Independence has a positive and significant effect on the quality of the review the financial statement of the Pinrang District Government; (3) Time pressure has a positive and significant effect on the quality of the review the financial statement of the Pinrang District Government. Keywords:     Auditor Professional Ethics; Independence; Time Pressure; Quality Of The Review.